2015
DOI: 10.1007/s10439-015-1430-4
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Elasticity Estimation in Pediatric Down Syndrome Sleep Apnea Patients Using Collapsible Tube Theory

Abstract: Elasticity of the soft tissues surrounding the upper airway lumen is one of the important factors contributing to upper airway disorders such as snoring and obstructive sleep apnea. The objective of this study is to calculate patient specific elasticity of the pharynx from Magnetic Resonance (MR) images using a ‘tube law’ i.e. the relationship between airway cross-sectional area and transmural pressure difference. MR imaging was performed under anesthesia in children with Down syndrome (DS) and obstructive sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Elasticity of the tissues surrounding the upper airways in individuals with DS is decreased, and lower stiffness is associated with an increased risk of obstruction [224] . Heterogeneous elasticity from a pharyngeal zone to another in a same individual can lead to numerous obstruction zones and an increased collapsibility [213] .…”
Section: A2 Cranio-facial Anthropometric Characteristicsmentioning
confidence: 99%
“…Elasticity of the tissues surrounding the upper airways in individuals with DS is decreased, and lower stiffness is associated with an increased risk of obstruction [224] . Heterogeneous elasticity from a pharyngeal zone to another in a same individual can lead to numerous obstruction zones and an increased collapsibility [213] .…”
Section: A2 Cranio-facial Anthropometric Characteristicsmentioning
confidence: 99%
“…Accordingly, to explore changes in the nasopalatine pharyngeal cavity in pediatric OSAHS, we performed upper airway MRI during sleep. As dynamic changes in soft palate morphology during respiration represent an important pathogenic factor in OSAHS, [ 17 ] we focused our studies on the nasopalatine pharyngeal cavity above the plane of the soft palate. In order to exclude multiple confounding factors, our study population included pediatric OSAHS patients with adenoidal hypertrophy alone.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that elasticity-based patient phenotyping can potentially assist clinicians in decision making on the level of continuous positive airway pressure. 39 Our study has several limitations that should be acknowledged. First, as already stated, the sample size was rather limited, which prevented the use of logistic regression and the comparison of FRI against clinical markers.…”
Section: Discussionmentioning
confidence: 92%